The National COPD Audit – what you need to know - Hurst, John R (Clin Med (Lond), 2019)
The secondary care work stream of the National COPD Audit Programme aims to improve care and outcomes for patients with exacerbation of chronic obstructive pulmonary disease (COPD) wherever and whenever they are admitted to hospital. To achieve this, prospective audit is combined with real-time feedback of data to individual units, together with support for quality improvement and high-level change levers. COPD exacerbations comprise a large proportion of the acute take. Only by working collaboratively across emergency, acute and general medicine, respiratory, geriatric and other teams can individual trusts deliver optimal care. This review provides background to the national COPD audit programme, relevant to all those caring for people with COPD exacerbations in secondary care.